2021
DOI: 10.1016/j.bspc.2021.102494
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and forecasting number of confirmed and death caused COVID-19 in IRAN: A comparison of time series forecasting methods

Abstract: Background The COVID-19 pandemic conditions are still prevalent in Iran and other countries and the monitoring system is gradually discovering new cases every day. Therefore, it is a cause for concern around the world, and forecasting the number of future patients and death cases, although not entirely accurate, helps the governments and health-policy makers to make the necessary decisions and impose restrictions to reduce prevalence. Methods In this study, we aimed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 21 publications
1
56
0
1
Order By: Relevance
“…From the beginning of 2020, an increasing body of literature has employed various approaches to forecast the spread of the COVID-2019 outbreak [ 9 , 22 , 26 , 58 , 73 , 78 , 79 , 83 , 85 ]. The most frequently used were ARIMA models [ 3 , 8 , 14 , 62 ], ETS models [ 13 , 44 ], artificial neural network (ANN) models [ 55 , 75 ], TBATS models [ 68 , 71 ], models derived from the susceptible–infected–removed (SIR) basic approach [ 22 , 26 , 58 , 78 , 85 ], and hybrid models [ 15 , 29 , 68 , 69 ]. The implementation and comparison of these approaches—with the exception of mechanistic–statistical models (such as SIR)—represents the core of this paper.…”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…From the beginning of 2020, an increasing body of literature has employed various approaches to forecast the spread of the COVID-2019 outbreak [ 9 , 22 , 26 , 58 , 73 , 78 , 79 , 83 , 85 ]. The most frequently used were ARIMA models [ 3 , 8 , 14 , 62 ], ETS models [ 13 , 44 ], artificial neural network (ANN) models [ 55 , 75 ], TBATS models [ 68 , 71 ], models derived from the susceptible–infected–removed (SIR) basic approach [ 22 , 26 , 58 , 78 , 85 ], and hybrid models [ 15 , 29 , 68 , 69 ]. The implementation and comparison of these approaches—with the exception of mechanistic–statistical models (such as SIR)—represents the core of this paper.…”
Section: Related Literaturementioning
confidence: 99%
“…Talkhi et al [ 71 ] attempted to forecast the number of COVID-19 confirmed infections and deaths in Iran between August 15, 2020, and September 14, 2020, using several single and hybrid models. The extreme learning machine (ELM) and hybrid ARIMA–NNAR models were the most suitable for forecasting confirmed cases, while the Holt–Winters (HW) approach outperformed the others in predicting death cases.…”
Section: Related Literaturementioning
confidence: 99%
“…This method is used for forecasting the univariate time series when the data might have both linear trend and seasonal pattern. In Holt-Winters exponential smoothing, recent observations are given relatively more weight than older observations; it is suitable for short-term forecasting and uses the maximum likelihood function for estimating parameters [21]. We calculated models that captured the evolving trend or seasonality of the data and extrapolated them into the future five-year period with 95% confidence prediction intervals.…”
Section: Forecasting Analysesmentioning
confidence: 99%
“…Talkhi et al [35] forecast the number of confirmed and death caused COVID-19 in Iran using nine different time series models, i.e. NNETAR, ARIMA, Hybrid, Holt-Winter, BSTS, TBATS, Prophet, MLP, and ELM network models.…”
Section: Introductionmentioning
confidence: 99%